RCM II Identifies Critical GTG Components and Maintenance Strategy: RCM II Mengidentifikasi Komponen GTG yang Kritis dan Strategi Pemeliharaan - Raihan Maulana Zulfikar; Rachmat Firdaus (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Gas Turbine Generator systems play a critical role in industrial power generation, where failures can cause significant operational and safety risks. Specific Background: Conventional maintenance strategies are often reactive and fail to prioritize component criticality, leading to inefficient resource allocation. Knowledge Gap: There is limited application of structured Reliability Centered Maintenance II integrated with Failure Mode and Effects Analysis to systematically identify failure risks and optimize maintenance strategies in GTG systems. Aims: This study aims to apply RCM II to determine critical components, analyze failure modes using FMEA, and define appropriate maintenance strategies based on risk levels. Results: The analysis identifies key components such as the compressor and combustion system as high-priority failure modes, with RPN values reaching 360 and 336 respectively. Other components fall into medium and low priority categories. Maintenance strategies are classified into proactive tasks using RCM II, simple FMEA-based actions, and run-to-failure approaches. Novelty: The study integrates RCM II decision diagrams with detailed RPN-based prioritization for GTG maintenance planning. Implications: The findings provide practical guidance for improving maintenance efficiency, optimizing labor allocation, and supporting reliable operation in industrial energy systems. Keywords: RCM II, Gas Turbine Generator, FMEA Analysis, Risk Priority Number, Maintenance Strategy Key Findings Highlights Risk evaluation highlighted dominant failure contributors in power generation unit Structured prioritization grouped components into three maintenance categories Decision-based tasks defined preventive and corrective operational actions